-2x+y+6=0

Simple and best practice solution for -2x+y+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+y+6=0 equation:


Simplifying
-2x + y + 6 = 0

Reorder the terms:
6 + -2x + y = 0

Solving
6 + -2x + y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -2x + -6 + y = 0 + -6

Reorder the terms:
6 + -6 + -2x + y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -2x + y = 0 + -6
-2x + y = 0 + -6

Combine like terms: 0 + -6 = -6
-2x + y = -6

Add '-1y' to each side of the equation.
-2x + y + -1y = -6 + -1y

Combine like terms: y + -1y = 0
-2x + 0 = -6 + -1y
-2x = -6 + -1y

Divide each side by '-2'.
x = 3 + 0.5y

Simplifying
x = 3 + 0.5y

See similar equations:

| 6.14x+36.84=73.68 | | 3x-14=3x+4 | | -x-1/5=6 | | 4+78x=39x+10 | | 16/-7=20/x | | a-5=3*a-5+1 | | X/-3-5=-9 | | -5(x+2)-17=11+7 | | 11x+4=12x-8 | | 10x+7y=36 | | 5/60=x/8 | | (-2+4i)-(3+9i)=0 | | 3a+19+15a+38= | | y=1/4x-4/3 | | 4x^2-16x= | | -10x-3(9-x)=4(-2x+5)-9 | | (3c-5)=(c+3) | | 6(2x+5)=102 | | 5(i+2)=2(r-4)-6 | | -11x4/7 | | 0.05x+0.20y= | | 5-a=a-5*3+1 | | -11x4z/7 | | 18x-6/3 | | -x+6=-8 | | y=13-3 | | 10x^2=134 | | 6p+20q+6= | | 0.3(n-5)=0.4-2(n-7) | | 10(7-x)=0 | | X(2y+3)+x(5y+4)= | | 0.05x+0.20y=4.20 |

Equations solver categories